Pengaruh Model Pembelajaran Conceptual Understanding Procedures (CUPs) Berbantuan LKPD Terhadap Kemampuan Pemecahan Masalah Fisika - Ibrahim Ibrahim; Kosim Kosim; Gunawan Gunawan (Department of Physics Education, Universitas Mataram, 2017)
This study aims to determine the effect of learning model Conceptual Understanding Procedures LKPD assisted on the ability of solving physics problems of high school students. This research is a quasi experimental research using untreated control group design with pretest and posttest. The population is all students of class XI IPA SMAN 4 Mataram. While the sampling using purposive sampling technique consisting of students class XI IPA 4 as experimental class and students of class XI IPA 1 as a control class. The problem solving capability data is obtained through a written test in the form of a description item. The result of hypothesis test analysis shows that there is influence of learning model of LKPD-assisted Conceptual Understanding Procedures toward the ability of problem solving physics.